Prevalence of green tobacco sickness (GTS) among tobacco farmer workers In Imogiri Sub-district, Bantul - Akmal Dwiyana Kau; Hari Kusnanto (Berita Kedokteran Masyarakat (BKM), 2017)
Background: Tobacco farmers are at risk to develop certain illness due to their work which is related to the absorption of nicotine from wet tobacco leaves through their skin. This illness is called Green Tobacco Sickness (GTS). Some factors that can increase the risk of GTS in tobacco farmers include the level of rainfall and high humidity, working hours (hour/ day), working period and lacking of using personal protective equipment. The purpose of this reserach is to find out the prevalence and the occurrence of GTS on tobacco farmers and the risk factors related to the occurrence of Green Tobacco Sickness between the tobacco farm workers.Method: This research is an analytical research by using cross sectional approach. The respondents in this research were as many as 10 tobacco farm workers in Selopamioro Sub-District, Imogiri District, Bantul. In order to find out the risk factors influencing the GTS occurrence on the tobacco farm workers, fisher exact test and mann whitney test was done in order to do the analysis.Results: This research found that the prevalence of Green Tobacco Sickness case in Selopamioro Sub-District was seven from ten tobacco farmers and percent of GTS was 70%. The factors of working hours (hour/day), working period (year), level of rainfall and the use of personal protective equipment had significant relation (p<0.05), while the variable of gender educational level, level of humidity did not have significant relation to the occurrence of GTS on the tobacco farmers in Selopamioro Sub-District (p>0.05).Conclusion: The results of the study found various risk factors that contribute to the occurrence of green tobacco sickness that is the level of education, the duration of work, the working period, and the use of personal protective equipment, therefore the use of personal protective equipment is important because it can protect farmers from symptoms of GTS, and the need for education Health concerns about health risks from cultivation to tobacco harvesting and ways to prevent GTS.